Решите уровнения. выражений 1). 3(х + 6) – х – 2(х + 9) = 2). 6 – 3(х + 1) – (7 – х) = 3). (8х + 3) – (10х - 6) – 9 = 4). 5 – 2(х - 1) – ( - 4 – х )= 5). (7х +1) – (9х + 3) + 5 = 6). (3,4 + 2у) - 7(у – 2,3) = 7). 4(5х + 2) - 10(3х - 3) + 15 = 8). 4(х - 1) - 2(2х - 8) + 12 = 9). 5,6 – 3(2 – 0,4х) - 0,4(4х - 1) = 10). 5(х - 12) + 6(х - 10) – (х - 1) = «решение линейных уравнений»1. вычисление неизвестного множителя 1). - 8х = 72 2). 0,9х = - 5,4 3). – 1,7х = - 5,1 4). 1/9 · х = - 8/9 5). - 2/7· х = - 1/6 6). - 6у = 48 7). 0,8х = - 3,2 8). – 1,6х = - 6,4 9). 1/7· х = - 3/4 10). – 4/9 · х = - 1/72. решение уравнений без скобок 1). х + 16 = 7 2). х + 5,8 = - 4,7 3). 5,5 – х = 12,9 4). – 8,8 – х = - 3,7 5). х – 9,21 = - 4,3 6). х + 12 = 5 7). – 5,4 – х = - 3,58). 2х = 18 - х 9). 7х + 3 = 30 – 2х 10). 7 – 2х = 3х – 18 11). 0,2х + 2,7 = 1,4 – 1,1х 12). 5,4 – 1,5х = 0,3х – 3,6 13). 11х = 36 – х 14). 9х + 4 = 48 – 2х 15). 8 – 4х = 2х - 16 16). 0,4х + 3,8 = 2,6 – 0,8х
1)x = ±2 3) x = ±3 5) x = ±1/7
2)y = ±3 4) y = ±2 6) y = ±1
Пошаговое объяснение:
1)[x] + 3 = 5 2)[y] - 2 =1 3) [2x] + 3 = 9
[x] = 5 - 3 [y] = 1+2 [2x] = 9 - 3
[x] = 2 [y] = 3 [2x] = 6
x = ±2 y = ±3 [x] = 6/2
[x] = 3
x = ±3
4) [5y] - 4 = 6
[5y] = 6+4
[5y] = 10
[y] = 10/5
[y] = 2
y = ±2
5)3/7 + [4x] = 1
[4x] = 1 - 3/7
[4x] = 4/7
[x] = 4/7 : 4
[x] = 1/7
x = ±1/7
6)4 + [3y] = 7
[3y] = 7 - 4
[3y] = 3
[y] = 3/3
[y] = 1
y = ±1